From Home to Classroom: Investigating Girls’ Participation in Secondary Level Mathematics - DC, Krishna; Rokaya, Bhim Bahadur (Academic Journal of Mathematics Education, 2023)
This study explores the nuanced journey of girls’ participation in secondary level mathematics, investigating the influences of early experiences at home and dynamics within the classroom. Focused on Grade IX students in Gurbhakot Municipality, Surkhet, the research adopts a quantitative approach through a survey design. Five secondary schools were selected using a convenience sampling method, aiming for diversity in community and geographical locations. Data collection involved Likert Scale points, encompassing 30 statements related to girls’ participation in mathematics. The analysis revealed key insights, including positive attitudes towards academic engagement, varied opinions on gender perceptions, strong familial support, favorable learning environments at home, and diverse views on societal and parental influences. The study’s significance lies in addressing a critical gap in literature by examining the transition from home to the classroom, offering valuable insights for educators and policymakers to enhance gender equity in mathematics education. The findings suggest areas for improvement, such as addressing gender perceptions, improving communication between parents and teachers, and enhancing the appeal of mathematics classes. Recognizing positive aspects, like strong family support and student interest, can contribute to fostering a more inclusive learning environment.